Modeling and simulation for the equilibrium of single mode fiber fusion - Ismail, Fairuz Diyana (2010)
Fabrication of fiber coupler using fusion requires stable torch flame. Stable torch flame is needed to have a good performance of fabrication. A model was required to observe the stable by equilibrium state of silicon dioxide fiber and nitrogen gas used for fabrication of fiber coupler. Continuity equation was applied to show the model of kinetic reaction derived from process of fiber molecule and nitrogen gas. Arrhenius equation form based on temperature variation and integration of kinetic model was examined. Validation of kinetic model towards thermodynamic equilibrium is evaluated by a zero dimensional and time dependence. Nitrogen species density is modelled by a continuity equation and extended form of Arrhenius equation. These equations were used to integrate the change of density over time. The integration was performed to acquire density and the reaction rate of each reaction where temperature and time dependence were imposed. A comparison was made with global model within pressure range of 1-100mTorr and the temperature of electron is set to be higher than other nitrogen species. Results show that the chemical kinetic model agrees only for high pressure because of no power imposition. The global model provides the power in the pressure range for electron and nitrogen at high density by a factor of 3 to 5. This model is plausible for evaluating experimental process in the fabrication of fiber coupler.